Comparing the Anglo-American and Israeli-American special relationships in the Obama era: an alliance persistence perspective - Xu, Ruike; Rees, Wyn (Taylor and Francis, 2016)
The Anglo-American and Israeli-American security relationships have proved to be unusually close and have confounded expectations that they would wither away with the changing international environment. In order to explain this, the article proposes a theory of ‘alliance persistence’ that is based on reciprocity over shared geostrategic interests, sentimental attachments and institutionalized security relations. The article employs this theoretical framework to explore how Anglo-American and Israeli-American relations have developed during the Obama administration. It argues that the Anglo-American relationship has been closer because of the two countries’ shared strategic interests, whilst the Israeli-American relationship has experienced divergences in how the security interests of the two sides have been pursued. The article concludes by assessing how the two relationships will fair in the post-Obama era and argues that there are numerous areas of tension in the US-Israeli relationship that risk future tensions. Keywords: Alliance, US-UK, US-Israel, Special Relationship, Obama